The effects of inspiratory muscle training on exercise capacity, dyspnea and respiratory functions in lung transplantation candidates: a randomized controlled trial - Pehlivan, Esra; Mutluay, Fatma; Balcı, Arif; Kılıç, Lütfiye (Clinical rehabilitation, 2018)
To investigate whether inspiratory muscle training would contribute to the improvement of exercise capacity, dyspnea perception and respiratory functions in lung transplantation candidates. Prospective randomized controlled trial. Pulmonary Rehabilitation center. A total of 34 patients with severe lung disease requiring lung transplantation were randomly allocated to either pulmonary rehabilitation plus inspiratory muscle training group (PR + IMT group, n = 17) or pulmonary rehabilitation group (PR group, n = 17) before any lung transplantation operation. All patients underwent supervised pulmonary rehabilitation program on two days per week for three months. The PR + IMT group received inspiratory muscle training in addition to the standard pulmonary rehabilitation program. The 6-minute walk test, maximal inspiratory pressure, modified Medical Research Concile dyspnea scores and spirometric parameters were measured for each patient. The PR + IMT group had statistically significantly increased in walking distance (100 m, P = 0.03), maximum inspiratory pressure (26 cmH O, P = 0.001) and alveolar volume ratio of carbonmonoxide diffusion capacity (9%, P = 0.02) than PR group. Although both groups demonstrated a statistically significant decrease in the dyspnea score, no significant differences were found between the groups ( P = 0.075). There was no change in spirometric variables in both groups. A greater increase in exercise capacity was observed in the PR + IMT group. Our study showed that inspiratory muscle training improved exercise capacity even further and increased the benefits provided by pulmonary rehabilitation.